A UK consensus algorithm for early treatment modification in newly diagnosed systemic light‐chain amyloidosis - Ravichandran, Sriram; Mahmood, Shameem; Wisniowski, Brenden; Sachchithanantham, Sajitha; Popat, Rakesh; Lachmann, Helen; Rabin, Neil; Ramasamy, Karthik; Hawkins, Stephen; Kyriakou, Charalampia; Gillmore, Julian; Yong, Kwee; et al. (British journal of haematology, 2022)
Summary Depth of response is the critical determinant of prognosis in amyloid light‐chain (AL) amyloidosis. Here, we aim to identify patients who are unlikely to improve response based on analysis of baseline characteristics and 1‐month response. In a multivariate model, difference in involved amyloidogenic and uninvolved serum free light chains (dFLC) at diagnosis (dFLC >400 mg/l, odds ratio [OR] 4.051, p < 0.005) and no response at 1 month (OR 4.787, p < 0.005) were significant predictors of no improvement in response. Only 5% of patients with a dFLC of >400 mg/l and no response at 1 month improved their response (p < 0.005). We suggest that these patients should switch treatment early, subject to their functional status.